2018
DOI: 10.1021/acs.jpclett.8b00800
|View full text |Cite
|
Sign up to set email alerts
|

Model of the Oxygen Evolving Complex Which Is Highly Predisposed to O–O Bond Formation

Abstract: Light-driven water oxidation is a fundamental reaction in the biosphere. The MnCa cluster of photosystem II cycles through five redox states termed S-S, after which oxygen is evolved. Critically, the timing of O-O bond formation within the Kok cycle remains unknown. By combining recent crystallographic, spectroscopic, and DFT results, we demonstrate an atomistic S state model with the possibility of a low barrier to O-O bond formation prior to the final oxidation step. Furthermore, the associated one electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
78
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 64 publications
(142 reference statements)
8
78
2
Order By: Relevance
“…A was assigned as the SFX structure by Okayama group (Suga et al ). Recent density functional theory (DFT) calculations (Beal et al , Pushkar et al ) also concluded the same assignment from their DFT calculations. However, the optimized Mn 4(a) ‐Mn 3(b) distance for Mn‐peroxide was about 2.96 Å in contradiction to the SFX result (2.74 Å by Suga et al () and 2.77 Å by Kern et al ()) as shown in Fig.…”
Section: Mn‐mn Mn‐o and O(5)‐o(6) Distances In The S3 Intermediates mentioning
confidence: 67%
“…A was assigned as the SFX structure by Okayama group (Suga et al ). Recent density functional theory (DFT) calculations (Beal et al , Pushkar et al ) also concluded the same assignment from their DFT calculations. However, the optimized Mn 4(a) ‐Mn 3(b) distance for Mn‐peroxide was about 2.96 Å in contradiction to the SFX result (2.74 Å by Suga et al () and 2.77 Å by Kern et al ()) as shown in Fig.…”
Section: Mn‐mn Mn‐o and O(5)‐o(6) Distances In The S3 Intermediates mentioning
confidence: 67%
“…Only recently was a combined EXAFS / ENDOR study able to suggest, based on Mn-Fe distance and absence of strong hyperfine coupling to hydrogen, that 4/4 possesses a di-μ-oxo Mn IV (O) 2 Fe IV core and terminal OH ligand bound to Mn. [7e] Previously, 4/3 was proposed to have a Mn IV (O)(OH)Fe III core, [7b, 8] suggesting the protonation pattern depicted in Scheme 1. These assignments rely, however, on indirect arguments, as intermetallic distances and absence of magnetic coupling are only proxies for the protonation state of the metallocofactor.…”
mentioning
confidence: 99%
“…Studies of such systems using element-specific x-ray spectroscopies typically involve serial measurement of each metal, a strategy that can lead to errors from sample variability and difficulty in assessing photoreduction of all metal centers. [7e] Serial data collection also multiplies required collection time and sample quantity, a nontrivial consideration with enzyme intermediates. Ideally, data from all metals in a heterometallic cofactor should be collected simultaneously.…”
mentioning
confidence: 99%
See 2 more Smart Citations